Essentials of Lewis's child and adolescent psychiatry - Volkmar, Fred R.; Martin, Andrés.; Lewis, Melvin, 1926-2007. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
"This body of work draws on various, sometimes distinctive and sometimes overlapping, historical and professional traditions, including the expanding knowledge about both normative child development and developmental processes as well as about the origins, expression, and treatment of psychopathology. Parts of the field have their origins in the social welfare movement and the concern for better approaches to juvenile justice"--Provided by publisher.
section I. Introduction -- section II. Normal development -- section III. Clinical disorders -- section IV. Treatment -- section V. Special issues.
Companion guide to: Lewis's child and adolescent psychiatry / editors, Andreś Martin, Fred R. Volkmar. 4th edition c2007.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Child development; Sick children -- Psychology; Child psychiatry; Electronic books